Using practitioners’ voices in developing a business rescue practitioner expert profile - Ayaya, Onesmus (Journal of Management and Business Education, 2024)
The study explored how business rescue (BR) practices can inform the development of an occupation profile needed to lay a foundation for developing business rescue practitioners’ occupation-specific qualifications. There are 11 professional organisations whose members qualify to serve as business rescue experts. The relevant occupation cannot have more than one occupation expert profile. The study employed qualitative approaches that entailed semi-structured interviews with 20 informants (12 business rescue practitioners, four short skills development programme (SSDP) managers, and 4 SSDP facilitators) and qualitative document content analysis of 30 court cases settled on the BR. The 12 business rescue practitioners (BRP) were randomly selected. However, other informants were accessed through a purposeful sample selection process. The field findings show that the BRP occupation in South Africa is a regulated practice area without an occupation expert profile. The BR practices have not been incorporated in a qualification framework registered on the Qualification Framework (NQF) governed by the South African Qualifications Authority (SAQA). Development of pipeline talent is limited, and the monitoring of SSDPs encounters limitations without an occupation expert profile and an occupation-specific qualification. The BR practices can be categorised into 11 tasks linked to practitioner training disciplines. The existing SSDPs provide an important mechanism for continuing professional development. However, the contents should be linked to BR practices and an occupation profile embracing the BRP role as an interim managing director in a business rescue process. The uniqueness of this article resides in its documentation of BR practices generated from multiple data sources that should be used to develop an occupation expert profile that reflects BRP’s capability. The setting of the BR process requires experts to operate in the capability realm. Methods: The study employed qualitative approaches that entailed semi-structured interviews with 20 informants (12 business rescue practitioners, four short skills development programme (SSDP) managers, and 4 SSDP facilitators) and qualitative document content analysis of 30 court cases settled on the BR. The 12 business rescue practitioners (BRP) were randomly selected. However, other informants were accessed through a purposeful sample selection process. Results: The field findings show that the BRP occupation in South Africa is a regulated practice area without an occupation expert profile. The BR practices have not been incorporated in a qualification framework registered on the Qualification Framework (NQF) governed by the South African Qualifications Authority(SAQA). Development of pipeline talent is limited, and the monitoring of SSDPs encounters limitations without an occupation expert profile and an occupation-specific qualification. The BR practices can be categorised into 11 tasks linked to practitioner training disciplines. Practical implications: The existing SSDPs provide an important mechanism for continuing professional development. However, the contents should be linked to BR practices and an occupation profile embracing the BRP role as an interim managing director in a business rescue process. Originality value: The uniqueness of this article resides in its documentation of BR practices generated from multiple data sources that should be used to develop an occupation expert profile that reflects BRP’s capability. The setting of BR process requires experts to operate in the capability realm. Keywords: business, expert, occupation, practitioner, practice, profile, rescue, voices.